Электрокинетические и агрегативные свойства модифицированных алмазных микро-, субмикро- и нанопорошков - Богатырева, Г.П.; Маринич, М.А.; Базалий, Г.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
Our present work has been aimed at developing modified micro-, submicro-, nano- diamond
powders. To modify the diamond surface thermochemical and electrochemical methods have been
used. Significants of dzeta-potential and aggregative properties of diamond powders were influenced
from type of modifications.